Plasma Levels of Advanced Glycation End Products Are Related to the Clinical Presentation and Angiographic Severity of Symptomatic Lower Extremity Peripheral Arterial Disease - Prasad, Anand; Lane, James R.; Tsimikas, Sotirios; Mahmud, Ehtisham; Khandrika, Srikrishna; Bekker, Peter; Ilapakurti, Manjusha; Nguyen, Dan; Ravandi, Amir; Israel, Travis (International Journal of Angiology, 2016)
Evidence implicates a role of advanced glycation end products (AGEs) in the development of atherosclerosis. The present study examined the relationship between plasma levels of AGEs and the clinical and angiographic characteristics of patients with symptomatic peripheral arterial disease (PAD). A total of 40 consecutive patients with symptomatic lower extremity PAD undergoing invasive evaluation were enrolled. Clinical history, angiographic data, and plasma levels of total AGE (tAGE), Nʹ-carboxymethyllysine (CML), and high-sensitivity C-reactive protein were obtained. In multivariate analyses, there were independent relationships noted between tAGE levels and the presence of critical limb ischemia (CLI) (r2 = 0.195, p = 0.003), Rutherford stage (r2 = 0.351, p < 0.001), and the average below the knee (BTK) score (r2 = 0.119, p = 0.006). Presence of CLI (r2 = 0.154, p = 0.012) and the Rutherford stage (r2 = 0.194, p = 0.003) were associated with CML levels. We demonstrate a relationship between tAGE and the symptom profile of patients with PAD and an association between tAGE and infrapopliteal angiographic disease severity. Both tAGE and CML levels were related to the presence of CLI. These data suggest that AGE levels may reflect the severity of PAD and may be of importance in CLI.
Keywords: peripheral arterial disease; advanced glycation; critical limb ischemia; atherosclerosis